ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦ä¸æ–‡ç³»2014å±Šå¦ç”Ÿä½¿ç”¨æ±‰è¯å‰¯è¯â€œå°±â€ä¸Žâ€œæ‰â€çš„åè¯¯åˆ†æž - Suryawaty, Yenny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractAdverbs are one of the most frequently used phrases in chinese and areÂ  important subject in chinese teaching for example, adverbs â€œjiuâ€ and â€œcaiâ€ are often used in everyday life. Based on the meaning, there are similarities and differences between the meaning of these three words that make students often wrong in using it. The author conducts a research on the students of class of 2014 Tanjungpura University in the use of adverbs â€œjiuâ€ and â€œcaiâ€. Based on the datas, the author analyzed the student error in using the two adverbs. Concluded that the percentage of misuse of â€œjiuâ€ and â€œcaiâ€ on student of class of 2014 University of Tanjungpura isÂ Â Â  40% and 33%. Common mistakes are word selection error is the influence of the mother tongue and the influence of the foreign languange being studied. Based on these findings, the author provides some suggestions for the learning of these two words.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Keywords: Adverbs â€œjiuâ€ and â€œcaiâ€, Error AnalysisÂ